Evaluation of dietary protein requirement for the growth performance of minor carp, Cirrhinus reba (Hamilton, 1822) fingerlings. (13th August 2019) - Yadav, Ajay Kumar; Mandal, Sagar Chandra; Patel, Arun Bhai; Maurya, Pradip Kumar
Abstract: An experiment was designed to evaluate the requirement of dietary protein for Reba carp, Cirrhinus reba fingerlings using semi‐purified diet. Five isocaloric diets were prepared containing 20%, 25%, 30%, 35% and 40% level of protein using casein, gelatin as a major protein source. The experiment was conducted for 105 days in triplicates to evaluate the growth, survival, feed utilization, carcass composition of C. reba . Mean weight gain was highest ( p < .05) in T3. Specific growth rate was highest in T3 and lowest in T1. Similarly, significantly ( p < .05) highest net fish yield were recorded in T3. No significant difference was recorded in survivability. Feed conversion ratio, protein efficiency ratio, feed conversion efficiency and protein conversion efficiency were significantly ( p < .05) higher for T3 compared with other treatments. Highest carcass protein and lipid values were recorded in T3. So, conclusion can be drawn that 30% crude protein is optimum for overall performance. Furthermore, broken‐line analysis for specific growth rate, final biomass and net fish yield indicated that dietary protein level of 28.148 to 28.253% is optimum for the best growth performance of fingerling C. reba .